Política econômica e trajetória da indústria no Brasil: Das origens à crise atual - Paccola, Marco Antonio Bestetti [UNESP] (2014)
The present study sought to trace the trajectory of industrial development in Brazil, from the policies for the sector as well as through major historical developments that were to influence the economy and in particular the industrial sector. We sought to understand how the development of the national economy led to the building of a complex industrial park in the country, as well as the struggles that took place behind the scenes of this development. The disputes within the ruling class and between both, internal and external economic groups, were present throughout the journey reassembled this analysis, as well as contribute to the explanation of the direction taken by the country. At the end we sought to contribute to the debate about the phenomenon of deindustrialization of the country to which the evidence be experiencing. A more detailed analysis was conducted on the period 2003-2010, during the height of commodity boom and appreciation of Brazil's trade balance, besides the political transition that this period represents. Thus, we intend to add to the current debate, important elements for understanding the situation in industry and general economic mode Brazil.